2022
DOI: 10.1155/2022/1590620
|View full text |Cite
|
Sign up to set email alerts
|

Application of Radiomics in Predicting Treatment Response to Neoadjuvant Chemoradiotherapy in Locally Advanced Rectal Cancer: Strategies and Challenges

Abstract: Neoadjuvant chemoradiotherapy (nCRT) followed by total mesorectal excision is the standard treatment for locally advanced rectal cancer (LARC). A noninvasive preoperative prediction method should greatly assist in the evaluation of response to nCRT and for the development of a personalized strategy for patients with LARC. Assessment of nCRT relies on imaging and radiomics can extract valuable quantitative data from medical images. In this review, we examined the status of radiomic application for assessing res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…Further, Cannella et al (19) suggested that magnetic resonance imaging (MRI)-based radiomics showed acceptable predictive performance, with an AUC of 0.791 for predicting the tumor response to TACE in 51 patients with HCC. At present, radiomicsrelated literature on HCC has identified various features and predictors for tumor response in several differently designed studies (multicenter versus single center), image segmentation methods (manual versus semi-automatic segmentation), imaging modality (CT or MRI), and predictive models (hand-crafted radiomics versus machine learning versus deep learning methods) (20). However, researchers have not yet reached a consensus on the most effective means to use radiomics to predict treatment response in patients with HCC who undergo TACE.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Cannella et al (19) suggested that magnetic resonance imaging (MRI)-based radiomics showed acceptable predictive performance, with an AUC of 0.791 for predicting the tumor response to TACE in 51 patients with HCC. At present, radiomicsrelated literature on HCC has identified various features and predictors for tumor response in several differently designed studies (multicenter versus single center), image segmentation methods (manual versus semi-automatic segmentation), imaging modality (CT or MRI), and predictive models (hand-crafted radiomics versus machine learning versus deep learning methods) (20). However, researchers have not yet reached a consensus on the most effective means to use radiomics to predict treatment response in patients with HCC who undergo TACE.…”
Section: Introductionmentioning
confidence: 99%